Emergency Mitral Valve Replacement in Blunt Cardiac Injury - Tkalich, Vasyl V.; Borysova, Valentyna I.; Savoliuk, Sergii I.; Kliuzko, Victor M.; Nedilia, Yurii V.; Galiiev, Oleksandr V. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Blunt Cardiac Injury (BCI) is a collective term that includes cardiac contusion, myocardial contusion, cardiac rupture, pericardial rupture, heart luxation, intracardiac structure injuries, coronary artery injuries, and injuries of the main vessels. Mitral valve injury due to blunt thoracic trauma is a very rare condition, accounting for only 0.01% of BCI cases. The clinical picture of hemodynamic instability in cases of mitral valve injury leads to pulmonary oedema (wheezing over the lung fields during auscultation) and progressive heart failure. Fluid overload increases the risk of death. Additional injuries can obscure the true cause of hemodynamic instability and shock. In the largest review of 82 patients who underwent surgery for mitral valve injury, only 15 patients (18%) were operated on within 24 hours. Aim. To present and analyze the case of emergency mitral valve replacement in first 24 hours in blunt chest trauma. Case report. In this study, we report the successful outcome of a blunt cardiac injury with mitral valve replacement performed within the first 24 hours. A 27-year-old male, a restrained driver, presented to the hospital in a state of shock. Hemorrhage as a cause of shock was excluded. Pulmonary oedema and worsening of the clinical picture despite resuscitation led to the diagnosis of an intracardiac injury as the cause of refractory shock. Urgent surgery with mitral valve replacement was performed within 24 hours of admission. The postoperative period was complicated by sepsis and ischemic stroke. The patient was discharged on the 44th day with mild rightsided hemiparesis. At the 24-month follow-up, clinical examination revealed no mitral insufficiency on cardiac echocardiography, and the patient had returned to his everyday activities. Conclusions. Surgical repair of mitral valve injuries is indicated when therapeutic or conservative treatment is unsuccessful. In other words, these patients have no chance of survival if surgery is not performed under such critical circumstances.